ANALISIS DAN PERBAIKAN SISTEM KOMPENSASI PADA KAFE ABC DENGAN SISTEM JOB POINT - Anggraini, Silviana; Elfriantika, Septia; Wulandari, Ressy Tri; Nugraha, Arlan; Nugraha, Dwi (KOLEGIAL, 2023)
Compensation is a factor that influences why and how people work in an organization. The research object of this group is Cafe ABC. ABC Café is a small and medium sized business engaged in the culinary field located in Pati Regency, Central Java. This UKM has 26 employees with 15 job titles including Restaurant Manager, R&D Manager, HR Manager, Head Kitchen, Head Service, Head Bar, Senior Chef, Junior Chef, Junior Barista, Purchasing Staff, Waitress, Social Media Admin, Cashier, Office Boy, Dishwasher. The research was conducted to analyze and educate the system for determining compensation for employees at the ABC Cafe in accordance with the Pati District Minimum Wage. The method for analyzing the compensation system is on the basis of job values ​​and job grading through salary mapping analysis which consists of two methods, namely overlapping and adhered. Based on the results of the research, the Adhered method is the right method for the compensation system for ABC Café employees.